Method for preparing 1100 aluminum alloy new energy battery aluminum foil from electrolytic aluminum liquid

1100 aluminum alloy was prepared by electrolytic aluminum liquid, combined with refined grains and cold rolling technology, the problems of low tensile strength and elongation of aluminum foil were solved, the performance of aluminum foil was improved, the technical requirements of new energy batteries were met, and the technical requirements of new energy batteries were reduced. Production cost.

CN119220861APending Publication Date: 2024-12-31GANSU JIUGANG & TIANCHENG COLOR ALUMINUM CO LTD
View PDF 0 Cites 4 Cited by

Patent Information

Application Number
CN202411389737.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-08
Publication Date
2024-12-31

AI Technical Summary

Technical Problem

The tensile strength and elongation of existing aluminum alloy batteries are low, resulting in low yield and increasing production costs, making it difficult to meet the demand for new energy vehicle batteries.

Method used

1100 aluminum alloy is prepared by electrolytic aluminum liquid. By refining grains, uniform casting and rolling strips, cold rolling processes, reasonably matching Fe, Cu, and Zn element ratios, and annealing treatment, the tensile strength and elongation of aluminum foil are improved. .

Benefits of technology

It achieves high tensile strength and elongation of aluminum foil, meets the technical indicators of new energy batteries, reduces production costs, and ensures the stability of product quality.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses a method for preparing an aluminum foil of a 1100 aluminum alloy new energy battery from electrolytic aluminum liquid. The aluminum foil comprises the following alloy elements in percentage by mass: 0.55 to 0.60 percent of Fe, 0.10 to 0.13 percent of Si, 0.20 to 0.25 percent of Cu, 0.010 to 0.020 percent of Ti, less than or equal to 0.01 percent of Mn, 0.015 to 0.025 percent of Zn, less than or equal to 0.01 percent of Mg and more than or equal to 99.00 percent of Al. And the high-strength aluminum foil is obtained through the processes of annealing, cold rolling, annealing and the like. The method has the beneficial effects that in large-scale industrial production, the product quality is stable, and the plate shape, the thickness difference, the surface quality and the mechanical property meet user requirements; the tensile strength of the prepared aluminum foil is 205-220 Mpa, the ductility is 4.5-6.0%, the tensile strength of the produced finished aluminum foil with the diameter of 0.012-0.015 microns is larger than or equal to 300 Mpa, and the ductility is larger than or equal to 3.0%.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of aluminum alloy smelting and processing, and in particular to a method for preparing 1100 aluminum alloy new energy battery aluminum foil by electrolyzing aluminum liquid. Background Art

[0002] New energy vehicles are listed as an important breakthrough in reducing carbon emissions. The automotive power batteries used in new energy vehicles are mainly lithium iron phosphate batteries and lithium electronic batteries. Battery aluminum foil is mainly used as the collector in these batteries, usually as the positive electrode collector and the composite film of the battery. This requires the aluminum foil to have high strength and good elongation. Usually, it is mainly based on 1××× series pure aluminum. This type of alloy has a low iron content and is easy to process. It is generally produced by the "casting or hot rolling + cold rolling" process, and a recrystallization annealing is performed during the cold rolling process to eliminate work hardening. However, the comprehensive mechanical properties of the aluminum foil blanks produced, such as tensile strength and elongation, are low. In the later processing, due to the low performance indicators, the battery yield is low, the production cost is increased, and it is difficult to meet production needs. Summary of the invention

[0003] The object of the present invention is to provide a method for preparing 1100 aluminum alloy new energy battery aluminum foil from electrolytic aluminum liquid, which has a simple processing and manufacturing method, is easy to process, has a low production cost, and has high tensile strength and improved elongation of the processed aluminum foil.

[0004] The invention discloses an 1100 aluminum alloy new energy battery aluminum foil. The mass ratio of each alloy element in the aluminum foil is: Fe: 0.55%-0.60%, Si: 0.10%-0.13%, Cu: 0.20%-0.25%, Ti: 0.010%-0.020%, Mn: ≤0.01%, Zn: 0.015%-0.025%, Mg: ≤0.01%, and Al≥99.00%.

[0005] The present invention discloses a method for preparing 1100 aluminum alloy new energy battery aluminum foil by electrolyzing aluminum liquid, which specifically comprises the following steps: S1: Refining grains and casting and rolling strip with uniform grain structure: S1.1. Increase nucleation points: Electrolytic aluminum liquid is used for preparation. To improve the purity of the product, the raw materials are aluminum liquid with Al ≥ 99.80% and remelted aluminum ingots with Al ≥ 99.80% as solid materials, of which the solid material mass accounts for ≥ 70% for loading into the furnace; S1.2. Modification and reduction of inclusions: During the smelting process, the alloy composition ratio uses aluminum-iron master alloy, fine copper cable or aluminum-copper master alloy, aluminum-silicon master alloy, zinc ingot, aluminum-titanium master alloy, and the mass proportion of Ti alloy component in the smelting furnace is controlled to be no higher than 0.008%; When the melt temperature reaches 745-755℃, refining begins. Each refining time is 30 minutes, and the refining interval is 3 hours. After refining, let it stand for 30 minutes and then skim the slag to the mirror surface. Then, heat it to 750-755℃ and pour the furnace. During the casting and rolling production process, a grain refiner is added at a single stage at the inlet of the degassing box, and the temperature of the aluminum liquid is 725±5℃. The grain refiner used meets the A-level control standard, and its Ti content is 4.8%-5.2%, B content is 0.9%-1.1%, Fe content is ≤0.20%, Si content is ≤0.15%, V content is ≤0.05%, and impurity element content is ≤0.10%. In addition, the average size of TiB2 particles in any 1cm3 longitudinal section is <2μm, and the distribution is roughly uniform and dispersed; in any 1cm3 longitudinal section, TiAl3 is blocky or rod-shaped, with an average particle size of <30μm, and the distribution is roughly uniform and dispersed. The total length of oxide inclusions shall not be greater than 1000μm, and there shall be no agglomerated or large pieces of TiB2, TiAl3 and oxide inclusions. S1.3. Casting and rolling production: The obtained melt is degassed, filtered and cast online to obtain a cast and rolling billet with a thickness of 6.8-8.0 mm; S1.3.1 Further, the length control range of the casting and rolling zone is set to 57-65mm, the opening of the casting nozzle is set to: 10-13mm, the casting and rolling speed is: 800-950mm / min, the cooling water temperature is: 35-40℃, and the rolling force is increased after the plate is successfully erected; S1.3.2 Further, the furnace eye temperature is controlled at 725-735°C, the degassing box temperature is 725-735°C, the filter box temperature is 715-725°C, and the front box temperature parameter range is 700±2°C; S2: The cold rolling process adopts the first pass high processing rate process after the billet opening pass and intermediate annealing. The cast strip obtained in step S1.3 is rolled at a pass processing rate of 60% and then intermediate annealing is performed. The roughness of the roller used is 0.65±0.02μm. The upper roller is convex and the lower roller is flat. The upper roller has a convexity of 0.03mm and the lower roller has a convexity of 0mm. The rolling speed is controlled at 200-350m / min. S2.1. The cast strip obtained in step S2 is heated to a metal temperature of 400-430°C at a furnace temperature of 530°C, and then transferred to a heat preservation stage for 4 hours and cooled out of the furnace; S2.2. The cast strip obtained in step S2.1 is processed at a temperature below 40°C at a processing rate of 60%, 54%, and 45%, and then naturally cooled and trimmed; the roughness of the roll used is 0.48±0.02μm, a double convex roll is used, the convexity of the upper roll is 0.02mm, the convexity of the lower roll is 0.02mm, and the rolling speed is controlled at 550-650m / min; S2.3. The strip obtained in step S2.3 is processed into a finished product at a processing rate of 34-37% and 30-35% at a temperature below 40°C, and then naturally cooled and trimmed. The strip is processed to H18 state according to the method, with a thickness of 0.20-0.22 mm. The tensile strength of the cast strip is detected to be Rm ≥ 210 MPa, and the elongation A50 is ≥ 3.5%. The 1100 aluminum alloy battery foil blank is processed; the roughness of the roller used is 0.35 ± 0.02 μm, and a double convex roller is used, with an upper roller convexity of 0.025 mm and a lower roller convexity of 0.025 mm. The rolling speed is controlled at 300-350 m / min; S3. Use plate filters to filter the dirty rolling oil generated during slab rolling, intermediate rolling and finished product rolling. The light transmittance of the filtered oil in the plate filter shall be ≥95%; S4. Foil rolling, the cold rolled blank obtained in step S2.3 is subjected to four passes of foil rolling to obtain a foil material of 0.012-0.015 mm; S5. Slitting, precision cutting, packaging and storage. The foil is slitting, precision cutting, packaging and storage according to the required specifications. During the process, pinhole defect online detection and corona treatment are carried out.

[0006] In the step S1.1, no more than 30% of the electrolytic aluminum liquid is used, and the rest is pure aluminum ingots.

[0007] In step S3, the filter aid in the plate filter is composed of diatomaceous earth, clay and cellulose, and the added mass ratio is 12.5:5:3; the filtration adopts bipolar filtration + tubular filtration, the filter plate specifications are 50ppi and 60ppi, and the tubular filtration adopts 11 filter tubes per group; In step S1.3, the specific passes of the casting and rolling production are distributed as follows: the first pass is rolled from 7.23mm to 3.5mm; the second pass is rolled from 3.5mm to 1.6mm, the third pass is rolled from 1.6mm to 0.88mm, the fourth pass is rolled from 0.88mm to 0.50mm, and the fifth pass is rolled from 0.50mm to 0.32mm; after the first pass, an intermediate annealing treatment is performed, and the furnace gas temperature is set to 530℃, and the temperature is raised to 400℃. The furnace gas temperature is adjusted to 400℃, and after keeping at this temperature for 4 hours, it is cooled with the furnace for 3 hours before being taken out of the furnace; after the fourth pass, the temperature is naturally lowered to a strip temperature below 40℃, and then the edge trimming treatment is performed.

[0008] The intermediate annealing method in step S2.1 adopts an annealing method in which the iron-containing compound is fully precipitated.

[0009] The beneficial effects of the present invention are: The present invention is based on the 1100 alloy in the national standard GB / T3190-2020, breaks the conventional idea of ​​alloy element ratio of high iron, high copper, low silicon and adding trace zinc elements, and proposes to produce 1100D alloy strip by direct continuous casting and rolling process technology of electrolytic aluminum liquid, and obtains a high-strength 1100D aluminum alloy new energy battery aluminum foil blank by reasonably matching Fe, Cu and Zn element ratios, and annealing, cold rolling, annealing and other process processes, which provides a guarantee for accurately controlling parameters in various links of production, and realizes stable product quality in large-scale industrial production. The plate shape, thickness difference, surface quality and mechanical properties meet user requirements. The high-strength 1100D aluminum alloy new energy battery aluminum foil blank prepared by the present invention has a tensile strength of 205-220Mpa and an elongation of 4.5-6.0%. The tensile strength of the finished aluminum foil of 0.012-0.015μm is ≥300Mpa, and the elongation is ≥3.0%, which meets the technical index requirements. DETAILED DESCRIPTION

[0010] The invention discloses an 1100 aluminum alloy new energy battery aluminum foil. The mass ratio of each alloy element in the aluminum foil is: Fe: 0.55%-0.60%, Si: 0.10%-0.13%, Cu: 0.20%-0.25%, Ti: 0.010%-0.020%, Mn: ≤0.01%, Zn: 0.015%-0.025%, Mg: ≤0.01%, and Al≥99.00%.

[0011] The present invention discloses a method for preparing 1100 aluminum alloy new energy battery aluminum foil by electrolyzing aluminum liquid, which specifically comprises the following steps: S1: Refining grains and casting and rolling strip with uniform grain structure: S1.1. Increase nucleation points: Electrolytic aluminum liquid is used for preparation. To improve the purity of the product, the raw materials are aluminum liquid with Al ≥ 99.80% and remelted aluminum ingots with Al ≥ 99.80% as solid materials, of which the solid material mass accounts for ≥ 70% for loading into the furnace; S1.2. Modification and reduction of inclusions: During the smelting process, the alloy composition ratio uses aluminum-iron master alloy, fine copper cable or aluminum-copper master alloy, aluminum-silicon master alloy, zinc ingot, aluminum-titanium master alloy, and the mass proportion of Ti alloy component in the smelting furnace is controlled to be no higher than 0.008%; When the melt temperature reaches 745-755℃, refining begins. Each refining time is 30 minutes, and the refining interval is 3 hours. After refining, let it stand for 30 minutes and then skim the slag to the mirror surface. Then, heat it to 750-755℃ and pour the furnace. During the casting and rolling production process, a grain refiner is added at a single stage at the inlet of the degassing box, and the temperature of the aluminum liquid is 725±5℃. The grain refiner used meets the A-level control standard, and its Ti content is 4.8%-5.2%, B content is 0.9%-1.1%, Fe content is ≤0.20%, Si content is ≤0.15%, V content is ≤0.05%, and impurity element content is ≤0.10%. In addition, the average size of TiB2 particles in any 1cm3 longitudinal section is <2μm, and the distribution is roughly uniform and dispersed; in any 1cm3 longitudinal section, TiAl3 is blocky or rod-shaped, with an average particle size of <30μm, and the distribution is roughly uniform and dispersed. The total length of oxide inclusions shall not be greater than 1000μm, and there shall be no agglomerated or large pieces of TiB2, TiAl3 and oxide inclusions. S1.3. Casting and rolling production: The obtained melt is degassed, filtered and cast online to obtain a cast-rolled billet with a thickness of 6.8-8.0 mm; S1.3.1 Further, the length control range of the casting and rolling zone is set to 57-65mm, the opening of the casting nozzle is set to: 10-13mm, the casting and rolling speed is: 800-950mm / min, the cooling water temperature is: 35-40℃, and the rolling force is increased after the plate is successfully erected; S1.3.2 Further, the furnace eye temperature is controlled at 725-735°C, the degassing box temperature is 725-735°C, the filter box temperature is 715-725°C, and the front box temperature parameter range is 700±2°C; S2: The cold rolling process adopts the first pass high processing rate process after the billet opening pass and intermediate annealing. The cast strip obtained in step S1.3 is rolled at a pass processing rate of 60% and then intermediate annealing is performed. The roughness of the roller used is 0.65±0.02μm. The upper roller is convex and the lower roller is flat. The upper roller has a convexity of 0.03mm and the lower roller has a convexity of 0mm. The rolling speed is controlled at 200-350m / min. S2.1. The cast strip obtained in step S2 is heated to a metal temperature of 400-430°C at a furnace temperature of 530°C, and then transferred to a heat preservation stage for 4 hours and cooled out of the furnace; S2.2. The cast strip obtained in step S2.1 is processed at a temperature below 40°C at a processing rate of 60%, 54%, and 45%, and then naturally cooled and trimmed; the roughness of the roll used is 0.48±0.02μm, a double convex roll is used, the convexity of the upper roll is 0.02mm, the convexity of the lower roll is 0.02mm, and the rolling speed is controlled at 550-650m / min; S2.3. The strip obtained in step S2.3 is processed into a finished product at a processing rate of 34-37% and 30-35% at a temperature below 40°C, and then naturally cooled and trimmed. The strip is processed to H18 state according to the method, with a thickness of 0.20-0.22 mm. The tensile strength of the cast strip is detected to be Rm ≥ 210 MPa, and the elongation A50 is ≥ 3.5%. The 1100 aluminum alloy battery foil blank is processed; the roughness of the roller used is 0.35 ± 0.02 μm, and a double convex roller is used, with an upper roller convexity of 0.025 mm and a lower roller convexity of 0.025 mm. The rolling speed is controlled at 300-350 m / min; S3. Use plate filters to filter the dirty rolling oil generated during slab rolling, intermediate rolling and finished product rolling. The light transmittance of the filtered oil in the plate filter shall be ≥95%; S4. Foil rolling, the cold rolled blank obtained in step S2.3 is subjected to four passes of foil rolling to obtain a foil material of 0.012-0.015 mm; S5. Slitting, precision cutting, packaging and storage. The foil is slitting, precision cutting, packaging and storage according to the required specifications. During the process, pinhole defect online detection and corona treatment are carried out.

[0012] In the step S1.1, no more than 30% of the electrolytic aluminum liquid is used, and the rest is pure aluminum ingots.

[0013] In step S3, the filter aid in the plate filter is composed of diatomaceous earth, clay and cellulose, and the added mass ratio is 12.5:5:3; the filtration adopts bipolar filtration + tubular filtration, the filter plate specifications are 50ppi and 60ppi, and the tubular filtration adopts 11 filter tubes per group; In the step S1.3, the specific passes of the casting and rolling production are distributed as follows: the first pass is rolled from 7.23mm to 3.5mm; the second pass is rolled from 3.5mm to 1.6mm, the third pass is rolled from 1.6mm to 0.88mm, the fourth pass is rolled from 0.88mm to 0.50mm, and the fifth pass is rolled from 0.50mm to 0.32mm; after the first pass, intermediate annealing treatment is carried out, the furnace gas temperature is set to 530℃, and after the temperature is raised to 400℃, the furnace gas temperature is adjusted to 400℃, and after keeping at this temperature for 4 hours, it is cooled with the furnace for 3 hours before being taken out of the furnace; after the fourth pass, the temperature is naturally lowered to a strip temperature below 40℃, and then edge trimming treatment is carried out.

[0014] The intermediate annealing method in step S2.1 adopts an annealing method in which the iron-containing compound is fully precipitated.

[0015] The 0.22mm thick aluminum foil blank prepared by the method for preparing 1100 aluminum alloy new energy battery aluminum foil from an electrolytic aluminum liquid of the present invention has a tensile strength of 210MPa-215MPa and an elongation of 4.5%-6.0%. When the double-sided light lithium ion battery foil with a thickness of 0.009mm is produced by foil rolling, the pass distribution is as follows: the first pass is pressed from 0.22mm to 0.10mm, the second pass is pressed from 0.10mm to 0.044mm, the third pass is pressed from 0.044mm to 0.023mm, and the fourth pass is pressed from 0.023mm to 0.012mm-0.015mm, and the tensile strength is 300MPa-320MPa and the elongation is 3.0%-4.0%. The produced aluminum foil greatly improves the tensile strength of the aluminum foil on the basis of ensuring the elongation.

Claims

1. A 1100 aluminum alloy new energy battery aluminum foil, characterized in that: The mass ratio of each alloy element in the aluminum foil is: Fe: 0.55%~0.60%, Si: 0.10%~0.13%, Cu: 0.20%~0.25%, Ti: 0.010%~0.020%, Mn: ≤0.01%, Zn: 0.015%~0.025%, Mg: ≤0.01%, Al≥99.00%.

2. A method for preparing 1100 aluminum alloy new energy battery aluminum foil from electrolytic aluminum liquid, characterized in that: The method specifically comprises the following steps: S1: Refining grains and casting and rolling strip with uniform grain structure: S1.

1. Increase nucleation points: Prepared by electrolytic aluminum liquid, the raw materials are aluminum liquid with Al ≥ 99.80% and remelted aluminum ingots with Al ≥ 99.80% as solid materials, of which the mass proportion of solid materials is ≥ 70%; S1.

2. Modification and reduction of inclusions: During the smelting process, the alloy composition ratio uses aluminum-iron master alloy, fine copper cable or aluminum-copper master alloy, aluminum-silicon master alloy, zinc ingot, aluminum-titanium master alloy, and the mass proportion of Ti alloy component in the smelting furnace is controlled to be no higher than 0.008%; When the melt temperature reaches 745-755℃, refining begins. Each refining time is 30 minutes, and the refining interval is 3 hours. After refining, let it stand for 30 minutes and then skim the slag to the mirror surface. Then, heat it to 750-755℃ and pour the furnace. During the casting and rolling production process, a grain refiner is added at a single stage at the inlet of the degassing box, and the temperature of the added aluminum liquid is 725±5℃; S1.

3. Casting and rolling production: The obtained melt is degassed, filtered and cast online to obtain a cast and rolling billet with a thickness of 6.8-8.0 mm; S1.3.

1. The length control range of the casting and rolling zone is set to 57-65mm, the opening of the casting nozzle is set to 10-13mm, the casting and rolling speed is 800-950mm / min, the cooling water temperature is 35-40℃, and the rolling force is increased after the plate is successfully erected; S1.3.

2. The furnace eye temperature is controlled at 725-735℃, the degassing box temperature is 725-735℃, the filter box temperature is 715-725℃, and the front box temperature parameter range is 700±2℃; S2: The cold rolling process adopts the first pass high processing rate process after the billet opening pass and intermediate annealing. The cast strip obtained in step S1.3 is rolled at a pass processing rate of 60% and then intermediate annealing is performed. The roughness of the roller used is 0.65±0.02μm. The upper roller is convex and the lower roller is flat. The upper roller has a convexity of 0.03mm and the lower roller has a convexity of 0mm. The rolling speed is controlled at 200-350m / min. S2.

1. The cast strip obtained in step S2 is heated to a metal temperature of 400-430°C at a furnace temperature of 530°C, and then transferred to a heat preservation stage for 4 hours and cooled out of the furnace; S2.

2. The cast strip obtained in step S2.1 is processed in three intermediate passes at a processing rate of 60%, 54% and 45% at a temperature below 40°C, and then naturally cooled and trimmed; the roughness of the roll used is 0.48±0.02μm, and a double convex roll is used, with an upper roll convexity of 0.02mm and a lower roll convexity of 0.02mm, and the rolling speed is controlled at 550-650m / min; S2.

3. The cast strip obtained in step S2.3 is processed into a finished product at a pass processing rate of 34-37% and 30-35% at a temperature below 40°C, and then naturally cooled and trimmed. The cast strip is processed to H18 state according to the method, and the thickness of the cast strip is 0.20-0.22mm. The tensile strength of the cast strip is Rm≥210MPa, and the elongation A50 is ≥3.5%. The 1100 aluminum alloy battery foil blank is processed; the roughness of the roller used is 0.35±0.02μm, and a double convex roller is used, with an upper roller convexity of 0.025mm and a lower roller convexity of 0.025mm. The rolling speed is controlled at 300-350m / min; S3. Use plate filters to filter the dirty rolling oil generated during slab rolling, intermediate rolling and finished product rolling. The light transmittance of the filtered oil in the plate filter shall be ≥95%; S4. Foil rolling, the cold rolled blank obtained in step S2.3 is subjected to four passes of foil rolling to obtain a foil material of 0.012-0.015 mm; S5. Slitting, precision cutting, packaging and storage. The foil is slitting, precision cutting, packaging and storage according to the required specifications. During the process, pinhole defect online detection and corona treatment are carried out.

3. The method for preparing 1100 aluminum alloy new energy battery aluminum foil from aluminum electrolysis liquid according to claim 1, characterized in that: In the step S1.1, no more than 30% of the electrolytic aluminum liquid is used, and the rest is pure aluminum ingots.

4. The method for preparing 1100 aluminum alloy new energy battery aluminum foil from aluminum electrolysis liquid according to claim 1, characterized in that: The filter aid in the plate filter described in S3. is composed of diatomaceous earth, clay and cellulose, and the added mass ratio is 12.5:5:

3.

5. The method for preparing 1100 aluminum alloy new energy battery aluminum foil from aluminum electrolysis liquid according to claim 1, characterized in that: In the step S1.3, the specific passes of the casting and rolling production are distributed as follows: the first pass is rolled from 7.23mm to 3.5mm; the second pass is rolled from 3.5mm to 1.6mm, the third pass is rolled from 1.6mm to 0.88mm, the fourth pass is rolled from 0.88mm to 0.50mm, and the fifth pass is rolled from 0.50mm to 0.32mm; after the first pass, intermediate annealing treatment is carried out, the furnace gas temperature is set to 530℃, and after the temperature is raised to 400℃, the furnace gas temperature is adjusted to 400℃, and after keeping at this temperature for 4 hours, it is cooled with the furnace for 3 hours before being taken out of the furnace; after the fourth pass, the temperature is naturally lowered to a strip temperature below 40℃, and then edge trimming treatment is carried out.

6. The method for preparing 1100 aluminum alloy new energy battery aluminum foil from aluminum electrolysis liquid according to claim 1, characterized in that: The intermediate annealing method in step S2.1 adopts an annealing method in which the iron-containing compound is fully precipitated.

Citation Information

Cited By

  • Aluminum foil for lithium ion battery and cast rolling production method of aluminum foil

    CN120485602A

  • Aluminum foil for lithium ion battery and cast-rolling production method thereof

    CN120485602B

  • High-extension aluminum foil for battery positive electrode and production method thereof

    CN120924842A

  • 1100 alloy battery aluminum foil with high elongation and low residual oil quantity and preparation method of 1100 alloy battery aluminum foil

    CN122235445A